Pengaruh Media Sosial Terhadap Pemasaran Produk UMKM Cemilan Bosque di Era Digital - Etty Zuliawati Zed; Rizky Muhammad Riyan; Abi Alpa Rijki (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to identify and analyze digital marketing strategies that are effective in increasing product sales in the online market. The research methods used include actor surveys of local businesses, and data analysis from digital platforms. Research results show that the use of social media, search engine optimization and content marketing play an important role in expanding market reach and attracting potential customers. Integrating e-commerce with digital marketing strategies such as paid advertising (PPC), email marketing, and influencer marketing has also proven effective in increasing sales. And the use of platforms such as Instagram, Shopee, TikTok has also been proven to increase sales in this digital era